2013
DOI: 10.1155/2013/153818
|View full text |Cite
|
Sign up to set email alerts
|

How Fatigue Is Experienced and Handled by Female Outpatients with Inflammatory Bowel Disease

Abstract: Background. Fatigue is a significant aspect of everyday life for patients with inflammatory bowel disease (IBD), and it influences their health-related quality of life. Little is known about fatigue from the patient's perspective. Aim. To investigate how female IBD patients experience and handle fatigue. Methods. The study included 11 female outpatients. These patients were 40–59 years old and had IBD ≥ one year and a significantly increased fatigue score. Patients with severe active IBD, anaemia, comorbidity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…50 Intense exercise increased systemic inflammation and the level of cytokines, resulting in worsened GI symptoms. 10 However, in a qualitative analysis, participants had different views about PA. 51 Some participants were actively engaged in exercise, and they reported having more energy. Conversely, others reported a vicious circle between fatigue and exercise, where low energy prohibited them from engaging in exercise, which led to a more sedentary life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Intense exercise increased systemic inflammation and the level of cytokines, resulting in worsened GI symptoms. 10 However, in a qualitative analysis, participants had different views about PA. 51 Some participants were actively engaged in exercise, and they reported having more energy. Conversely, others reported a vicious circle between fatigue and exercise, where low energy prohibited them from engaging in exercise, which led to a more sedentary life.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, others reported a vicious circle between fatigue and exercise, where low energy prohibited them from engaging in exercise, which led to a more sedentary life. 51 Therefore, a dose-effect approach should be considered with PA/exercise in adults with IBD when considering the type of exercise, the intensity, and the duration. 10 Additionally, disease activity can be a con-founding factor and patients with mild form of disease activity may engage in exercise more frequently resulting in improved IBD outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Relatives play in important role in the process of acceptance of fatigue, as their acceptance of and support in managing disease related symptoms, such as fatigue, are highly valued by IBD patients. (Beck et al, 2013) one study suggested that lower social support was related to decline in 'vigour' in individuals with UC (Tanaka and Kazuma, 2005), however these findings are not supported by more recent evidence. (Simrén et al, 2008;Opheim, Fagermoen, Bernklev, et al, 2014;Norton et al, 2015) The management of long-term conditions (LTC) such as IBD, is widely acknowledged as one of the principal challenges facing the 21 st century National Health Service (NHS).…”
mentioning
confidence: 81%
“…On the other hand, previous studies suggested that IBD sufferers have a tendency to refrain from talking about their typical symptoms, such as fatigue, to health professionals and even their own family members and friends (Beck et al, 2013;Hall et al, 2005). Gastroenterology nurses and midwives should focus on these tendencies, consider the health-related and learning needs of IBD women, and offer them opportunities to express their feelings or concerns during the perinatal period.…”
Section: Roles Of Health Professionals Involved In Care Of Women Withmentioning
confidence: 99%